Silicon-based resin composition and semiconductor device including the same

KR1020260134749APending Publication Date: 2026-09-09WACKER CHEMIE AG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020267026760
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-02-27
Publication Date
2026-09-09

Smart Images

  • Figure P1020267026760_ABST
    Figure P1020267026760_ABST
Patent Text Reader

Abstract

The present invention provides a silicone-based resin composition comprising an organic polysiloxane; a conductive filler; and a curing catalyst, wherein the conductive filler comprises a dendrite-type conductive powder having a main axis with an average length of 20 μm to 50 μm and a plurality of minor axes branched from the main axis, and the thermal conductivity value per unit volume of the silicone-based resin composition is expressed by the following Equation 1 (see detailed description) and is 10 to 40.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a silicon-based resin composition and a semiconductor device including the same. Background Technology

[0002] Since most electronic components generate heat during use, removing that heat is essential for their normal operation. In particular, the amount of heat generated by integrated circuit components, such as CPUs used in personal computers, is increasing due to faster operating frequencies, making heat dissipation measures a critical challenge.

[0003] Therefore, various methods for heat dissipation have been proposed, and for electronic components with a large amount of heat dissipation, a method has been proposed to dissipate heat by interposing a thermally conductive material, such as thermally conductive grease or a thermally conductive sheet, between the electronic component and a component such as a heat sink.

[0004] Korean Published Patent No. 10-2020-0086307 discloses a semiconductor device comprising a thermally conductive material.

[0005] [Related Technical Literature]

[0006] [Patent Literature]

[0007] (Patent Document 1) Korean Published Patent No. 10-2020-0086307 The problem to be solved

[0008] Accordingly, the present invention has been made in consideration of the above problems, and one objective of the present invention is to provide a silicon-based resin composition capable of realizing high thermal conductivity and providing excellent heat dissipation characteristics due to an improved coverage rate; and a semiconductor device comprising such silicon-based resin composition. means of solving the problem

[0009] According to one aspect of the present invention, the above and other objectives can be achieved by providing a silicone-based resin composition comprising an organic polysiloxane; a conductive filler; and a curing catalyst, wherein the conductive filler comprises a dendrite-type conductive powder comprising a main axis having an average length of 20 μm to 50 μm and a plurality of minor axes branched from the main axis, and the thermal conductivity value per unit volume of the silicone-based resin composition is expressed by Equation 1 below and is 10 to 40:

[0010]

[0011] In the equation, V is the volume ratio of the conductive filler to the total volume of the silicone-based resin composition and is a unitless value, and TC is the thermal conductivity measured by measurement method 1 below and is a unitless value:

[0012] [Measurement Method 1]

[0013] 1) A silicone-based resin composition is molded into a size of 30 mm x 30 mm x 4 mm by a heat press.

[0014] 2) Next, the molded silicone-based resin composition is cured at 150°C for 2 hours to prepare a sample.

[0015] 3) Measure the thermal conductivity of the sample at 25℃ according to ISO 22007-2.

[0016] In one embodiment of the present invention, the conductive powder may have an aspect ratio of 10 to 50.

[0017] In one embodiment of the present invention, the conductive powder has a tapped density of 2.0 g / cm³ 3 It may be less than

[0018] In one embodiment of the present invention, the conductive powder has an average particle diameter (D 50 A first conductive powder having a diameter of 10 μm to 20 μm and an average particle diameter (D50 It may include a second conductive powder with a thickness of 1 μm or more and less than 10 μm.

[0019] In one embodiment of the present invention, the first conductive powder has a specific surface area of ​​0.2 m² 2 / g to 1.0 m 2 It can be / g.

[0020] In one embodiment of the present invention, the second conductive powder has a specific surface area of ​​0.8 m² 2 / g to 2.0 m 2 It can be / g.

[0021] In one embodiment of the present invention, the thermal conductivity (TC) may be 7 W / mK or higher.

[0022] In one embodiment of the present invention, the lap shear strength of the silicone-based resin composition, when measured according to DIN EN 1465, is 0.5 N / mm 2 It could be more than that.

[0023] In one embodiment of the present invention, the junction separation length may be 0.3 mm or more when measured according to DIN EN 1465.

[0024] In one embodiment of the present invention, the coverage rate of the silicone-based resin composition may be 90% or more when measured by the measurement method 2 below:

[0025] [Measurement Method 2]

[0026] 1) A silicone-based resin composition is coated onto a first silicon substrate with dimensions of 27 mm x 27 mm at a weight of 0.7 g.

[0027] 2) A second silicon substrate of the same or larger size as the first silicon substrate is placed on the coated silicon-based resin composition, and then the silicon-based resin composition is cured while compressed by a force of 3 kgf.

[0028] 3) The area where the first silicon substrate is in close contact with the second silicon substrate is determined by the cured silicone-based resin composition. And

[0029] 4) The coverage ratio is the ratio of the area of ​​the first silicon substrate in contact with the second silicon substrate to the planar area of ​​the first silicon substrate.

[0030] According to another aspect of the present invention, a semiconductor device is provided comprising: a semiconductor package; a heat dissipation portion disposed on the semiconductor package; and a thermal conductive layer interposed between the semiconductor package and the heat dissipation portion, wherein the thermal conductive layer comprises a silicon-based resin composition, the silicon-based resin composition comprises an organic polysiloxane, a conductive filler, and a curing catalyst, and the conductive filler comprises a dendrite-type conductive powder comprising a main axis having an average length of 20 μm to 50 μm and a plurality of minor axes branched from the main axis, and the thermal conductivity value per unit volume of the silicon-based resin composition is expressed by the following Equation 1 and is 10 to 40:

[0031]

[0032] In the equation, V is the volume ratio of the conductive filler to the total volume of the silicone-based resin composition and is a unitless value, and TC is the thermal conductivity measured by measurement method 1 below and is a unitless value:

[0033] [Measurement Method 1]

[0034] 1) A silicone-based resin composition is molded into a size of 30 mm x 30 mm x 4 mm by a heat press.

[0035] 2) Next, the molded silicone-based resin composition is cured at 150°C for 2 hours to prepare a sample.

[0036] 3) Measure the thermal conductivity of the sample at 25℃ according to ISO 22007-2.

[0037] [Advantageous Effects]

[0038] The silicone-based resin composition according to the present invention comprises a dendrite-type conductive powder comprising a main axis having an average length of 20 μm to 50 μm and a plurality of sub-axiss branched from the main axis, and the thermal conductivity value per unit volume of the silicone-based resin composition satisfies 10 to 40.

[0039] Therefore, the silicone-based resin composition according to the present invention can achieve high thermal conductivity even when using a small amount of conductive filler, so the heat dissipation function can be improved.

[0040] In addition, the cured product of the silicone-based resin composition according to the present invention can achieve high thermal conductivity and, at the same time, can have an improved coverage rate and an appropriate spread thickness.

[0041] Therefore, when a silicon-based resin composition is used in a semiconductor device, the silicon-based resin composition can be coated with a uniform thickness between the semiconductor package and the heat dissipation part, thereby improving the heat dissipation function. Brief explanation of the drawing

[0042] Figure 1 is a cross-sectional view showing the process of measuring the wrap shear strength and bond separation length of a silicone-based resin composition. FIG. 2 is a cross-sectional view illustrating a cross-section of a semiconductor device according to one embodiment. Specific details for implementing the invention

[0043] The structural or functional descriptions of the embodiments disclosed in this specification or application are merely examples for explaining embodiments according to the technical concept of the present invention, and embodiments according to the technical concept of the present invention may be implemented in various forms other than those disclosed in this specification or application, and the technical concept of the present invention should not be interpreted as being limited to the embodiments described in this specification or application.

[0044] In this specification or application, when a specific part "comprising" a specific component, it indicates that, unless otherwise specified, such part does not exclude other components but may include them further. Furthermore, it should be understood that all numerical ranges representing physical property values, dimensions, etc., of components described in this specification or application are always modified by the term "approximately" unless otherwise specified.

[0045] In this specification or application, when any part, surface, layer, or substrate is referred to as being "on" or "below" another part, surface, layer, or substrate, said part, surface, layer, or substrate may be directly on the other part, surface, layer, or substrate, or may be on an interposed part, surface, layer, or substrate, and the criteria for "on" and "below" will be provided based on the drawings. Elements in the following drawings may be exaggerated, omitted, or schematically depicted for convenience and clarity of description, and the size of the elements does not fully reflect their actual size.

[0046] Now, a silicon-based resin composition according to the present invention and a semiconductor device including the same are described.

[0047] The silicone-based resin composition according to the present invention comprises an organic polysiloxane.

[0048] Organic polysiloxanes can be represented by the following Formula 1:

[0049]

[0050] In Equation 1, R 1 It may represent one or more groups selected from the group consisting of hydrogen atoms, hydroxyl groups, and saturated or unsaturated monovalent hydrocarbon groups having 1 to 18 carbon atoms, and a may be about 1.8 to about 2.2. a+b may be about 3.5 to about 8.

[0051] a+b can be 4.

[0052] In Equation 1, R 1 A saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms represented by may be, for example, an alkyl group such as a methyl group, ethyl group, propyl group, hexyl group, octyl group, decyl group, dodecyl group, tetradecyl group, hexadecyl group, or octadecyl group; a cycloalkyl group such as a cyclopentyl group or cyclohexyl group; an alkenyl group such as a vinyl group or an allyl group; an aryl group such as a phenyl group or a tolyl group; an aryl group such as a 2-phenylethyl group or a 2-methyl-2-phenylethyl group; or a halogenated hydrocarbon group such as a 3,3,3-trifluoropropyl group, a 2-(perfluorobutyl)ethyl group, a 2-(perfluorooctyl)ethyl group, or a p-chlorophenyl group.

[0053] The organic polysiloxane may have a weight-average molecular weight of about 40,000 g / mol to about 80,000 g / mol, about 30,000 g / mol to about 100,000 g / mol, about 500 g / mol to about 10,000 g / mol, about 700 g / mol to about 7,000 g / mol, about 1,000 g / mol to about 5,000 g / mol, or about 1,500 g / mol to about 3,000 g / mol. The weight-average molecular weight may be measured based on polystyrene.

[0054] In organic polysiloxanes, the kinematic viscosity at 25°C is 10 mm 2 / s to 100,000 mm 2 / s, 20,000 mm 2 / s to 100,000 mm 2 / s, or about 30 mm 2 / s to about 10,000 mm 2 It may be / s. The kinematic viscosity of the organic polysiloxane may be the value at 25°C measured with an Ostwald viscometer.

[0055] When the weight average molecular weight and kinematic viscosity of the organic polysiloxane are within the above ranges, it can maintain appropriate adhesion strength to the adherend and improve durability by preventing voids and cracks caused by thermal shock.

[0056] The organic polysiloxane may include a first organic polysiloxane.

[0057] The first organic polysiloxane comprises alkenyl groups bonded to silicon atoms. At least two, two to ten, two to five, or two alkenyl groups may be present in one molecule of the first organic polysiloxane.

[0058] The first organopolysiloxane can be represented by the following Formula 2:

[0059]

[0060] In Equation 2, R 1 It may be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, and R 2 may be an alkenyl group. In Formula 2, a+c may be about 1.8 to about 2.2, and a+b+c may be about 3.5 to about 8. In Formula 2, a+b+c may be about 4. In Formula 2, a may be about 1.8 to about 2.2. Also, c may be 0.0001 to 0.1.

[0061] The first organopolysiloxane can be represented by the following Formula 3:

[0062]

[0063] In Equation 3, R 1 It may be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, and R 2can be an alkenyl group. Also, in Equation 3, n can be 1 to 1,500 and m can be 0 to 20. In Equation 3, n can be 10 to 1,000 and m can be 0 to 20.

[0064] The first organopolysiloxane can be represented by the following Formula 4:

[0065]

[0066] In Equation 4, n can be from 1 to 1,500. n can be from 10 to 1,000.

[0067] The first organopolysiloxane may have a weight-average molecular weight (Mw) of about 500 g / mol to about 10,000 g / mol, about 700 g / mol to about 7,000 g / mol, about 1,000 g / mol to about 5,000 g / mol, or about 1,500 g / mol to about 3,000 g / mol. The weight-average molecular weight may be measured based on polystyrene.

[0068] In the first organic polysiloxane, the kinematic viscosity at 23°C may be 10 cPs to 100,000 cPs, 30 cPs to 50,000 cPs, or 10,000 cPs to 40,000 cPs. The kinematic viscosity of the first organic polysiloxane may be a value at 23°C measured by an Ostwald viscometer.

[0069] The organic polysiloxane may include a second organic polysiloxane.

[0070] The second organic polysiloxane may include hydrogen groups bonded to silicon atoms. The number of hydrogen groups per molecule of the second organic polysiloxane may be 1 to 10, 2 to 10, 2 to 5, or 2.

[0071] The second organopolysiloxane can be represented by the following Formula 5:

[0072]

[0073] In Equation 5, R 1 It may be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, and R 3 It can be a hydrogen atom. Also, in Equation 5, n can be 1 to 1,500 and m can be 0 to 20. In Equation 5, n can be 10 to 1,000 and m can be 0 to 20. In Equation 5, n can be 1 to 1,500 and m can be 0.

[0074] The second organopolysiloxane can be represented by the following Formula 6:

[0075]

[0076] At about 23°C, the viscosity of the second organic polysiloxane may be about 500 cPs to about 5,000 cPs, about 500 cPs to about 3,000 cPs, or about 500 cPs to about 2,000 cPs.

[0077] The organic polysiloxane may further comprise a third organic polysiloxane. The third organic polysiloxane can be represented by the following Formula 7:

[0078]

[0079] In Equation 7, R 1 It may be a hydrogen atom, a hydroxyl group, or a saturated or unsaturated monovalent hydrocarbon group having 1 to 18 carbon atoms, and R 3 It can be a hydrogen atom. Also, in Equation 7, n can be 1 to 1,500 and m can be 1 to 500. In Equation 7, n can be 10 to 1,000 and m can be 1 to 100.

[0080] The tertiary organopolysiloxane can be represented by the following Formula 8:

[0081]

[0082] In Equation 8, n can be 1 to 1,500 and m can be 1 to 500. In Equation 8, n can be 10 to 1,000 and m can be 1 to 100.

[0083] At about 23°C, the viscosity of the third organic polysiloxane may be about 50 cPs to about 1,000 cPs, about 100 cPs to about 500 cPs, or about 100 cPs to about 500 cPs.

[0084] The ratio of the viscosity of the first organic polysiloxane to the viscosity of the second organic polysiloxane may be 10:1 to 40:1.

[0085] In addition, the ratio of the viscosity of the second organic polysiloxane to the viscosity of the third organic polysiloxane may be 2:1 to 10:1.

[0086] The content of the first organic polysiloxane may be about 60 to about 90 parts by weight, about 70 to about 85 parts by weight, or about 75 to about 85 parts by weight, based on 100 parts by weight of the total organic polysiloxane.

[0087] The content of the second organic polysiloxane may be about 10 to about 40 parts by weight, about 10 to about 30 parts by weight, or about 12 to about 23 parts by weight based on 100 parts by weight of the first organic polysiloxane.

[0088] The content of the third organic polysiloxane may be about 3 to about 20 parts by weight, about 3 to about 15 parts by weight, or about 4 to about 10 parts by weight based on 100 parts by weight of the first organic polysiloxane.

[0089] When a silicone-based resin composition contains a first organic polysiloxane, a second organic polysiloxane, and a third organic polysiloxane within a certain range, it can maintain proper adhesion to a substrate and spread evenly during the coating process.

[0090] The silicone resin composition includes a conductive filler.

[0091] Previously, spherical conductive powders were used to improve the heat dissipation characteristics of silicone-based resin compositions. However, due to the small surface area of ​​the spherical conductive powders and the resulting low contact characteristics between the powder particles, there were limitations in achieving excellent heat dissipation characteristics.

[0092] To improve heat dissipation characteristics, the thermal conductivity of silicon-based resin compositions was improved using flake-type and / or dendrite-type conductive powders, but there was a problem with low dispersibility due to high agglomeration. In addition, silicon-based resin compositions containing flake-type and / or dendrite-type conductive powders have a significantly reduced coverage rate, so when the silicon-based resin composition is used as a thermal conductive layer in a semiconductor device, the area in close contact with the semiconductor package and the heat dissipation part is reduced, which leads to a problem of degraded heat dissipation characteristics.

[0093] Accordingly, the inventors have confirmed that when a conductive filler comprises a dendrite-type conductive powder having a main axis with an average length of 20 μm to 50 μm and a plurality of sub-axiss branched from the main axis, and the thermal conductivity value per unit volume of the silicone-based resin composition expressed by Equation 1 below satisfies 10 to 40, high thermal conductivity can be achieved even when using a small amount of conductive filler, and an improved coverage rate and appropriate spreading thickness can be achieved, resulting in excellent heat dissipation characteristics.

[0094]

[0095] In Equation 1, V is the volume ratio of the conductive filler to the total volume of the silicone-based resin composition and is a value excluding units, and TC is the thermal conductivity measured by the measurement method 1 below and is a value excluding units.

[0096] [Measurement Method 1]

[0097] 1) A silicone-based resin composition is molded into a size of 30 mm x 30 mm x 4 mm by a heat press.

[0098] 2) Next, the sample is prepared by curing it at 150°C for 2 hours.

[0099] 3) Measure the thermal conductivity of the sample at 25℃ according to ISO 22007-2.

[0100] The dendrite-type conductive powder may be an aggregate of dendrite-type conductive particles, and the dendrite-type conductive particles may have a shape including one main axis and a plurality of sub-axiss branched from this main axis.

[0101] The dendrite-type conductive particle may have a shape including a plurality of sub-axes branched from the main axis with the main axis as the axis of symmetry.

[0102] The average length of the principal axis of the dendrite-type conductive particles may be 20 μm to 50 μm, 21 μm to 50 μm, 22 μm to 50 μm, or 22 μm to 45 μm.

[0103] The average length of the principal axis can be calculated by observing 100 particles in 15 fields of view at a magnification of 15,000x using a scanning electron microscope and calculating the average value.

[0104] Since the silicone-based resin composition includes dendrite-type conductive powder having a principal axis average length within a range, the contact characteristics between the powders can be improved, and the kneading characteristics with organic polysiloxane can be improved, thereby improving the heat dissipation characteristics.

[0105] Thermal conductivity per unit volume can be an indicator of the possibility of delamination of the thermal conductive layer caused by shear stress and the potential to perform an appropriate heat dissipation function.

[0106] When a silicone-based resin composition includes dendrite-type conductive powder as a conductive filler and the volume ratio of the conductive powder to the total volume of the silicone-based resin composition increases, the thermal conductivity may be improved. However, the dispersibility of the conductive powder may be reduced, and the volume ratio of the organic polysiloxane may be relatively reduced, which may increase the possibility of delamination of the thermal conductive layer due to shear stress.

[0107] Meanwhile, if the volume ratio of the conductive powder to the total volume of the silicone-based resin composition is reduced, the dispersibility of the conductive powder is improved, and the volume ratio of the organic polysiloxane is relatively increased, the possibility of delamination of the thermal conductive layer caused by shear stress can be suppressed. However, since the contact characteristics between the conductive powders are degraded, the thermal conductivity is reduced, making it difficult to perform an appropriate heat dissipation function.

[0108] In other words, as the thermal conductivity per unit volume increases, the possibility of delamination of the thermal conductive layer caused by shear stress may increase, whereas as the thermal conductivity per unit volume decreases, the possibility of deterioration in thermal conductivity and heat dissipation characteristics may increase.

[0109] Accordingly, the present invention selected a dendrite-type conductive powder among various types of conductive powders. By adjusting the average length of the main axis of the dendrite-type conductive powder to 20 μm to 50 μm and the thermal conductivity per unit volume to 10 to 40, high thermal conductivity can be achieved with a small amount of conductive filler, and an improved coverage rate and appropriate spreading thickness can be achieved, thereby suppressing the possibility of delamination of the thermal conductive layer.

[0110] The thermal conductivity (TC) value may be 7 W / mK or higher, 7.5 W / mK or higher, 8 W / mK or higher, 8.5 W / mK or higher, or 7 W / mK to 9.5 W / mK.

[0111] The thermal conductivity value per unit volume may be 10 to 40, 15 to 40, 20 to 40, or 20 to 35.

[0112] If the range is satisfied, high thermal conductivity can be achieved and the coverage rate can be improved, thereby improving heat dissipation characteristics.

[0113] The conductive powder may include at least one of inorganic particles or metal particles.

[0114] The conductive powder may contain silver (Ag) powder. The silver content relative to the total weight of the conductive powder may be 80 wt%, 85 wt%, 90 wt%, 95 wt%, or 99 wt%. Preferably, the silver content in the conductive powder may be 99 wt% or more.

[0115] Preferably, the conductive powder may not contain copper. If the conductive powder contains copper, the conductive powder may oxidize during the high-temperature curing process of the silicone-based resin composition. Additionally, if the conductive powder is exposed to air after the silicone-based resin composition has cured, an oxide film may easily form on the copper surface. Oxidized conductive powder may reduce thermal conductivity.

[0116] The conductive powder may have an aspect ratio of 10 to 50, 10 to 45, 10 to 40, or 10 to 30.

[0117] The aspect ratio is defined as the value obtained by dividing the length of the particle's major axis by the length of its minor axis.

[0118] The conductive powder is 2.0 g / cm³ 3 Less than, 1.8 g / cm³ 3 Below, 1.5 g / cm³ 3 Less than or equal to 0.1 g / cm³ 3 Up to 1.0 g / cm³ 3 It can have a tapped density.

[0119] To obtain the tap density, approximately 100 g of conductive powder is weighed and gently dropped into a 100 ml graduated cylinder using a funnel, then the cylinder is placed in a tap density meter and the conductive powder is compressed by dropping it 600 times at a rate of 60 times per minute from a drop distance of 20 mm. The tap density is calculated from the volume of the compressed conductive powder.

[0120] The conductive powder has an average particle diameter (D) of 1 μm to 20 μm, 1 μm to 18 μm, 2 μm to 18 μm, or 3 μm to 18 μm. 50 Can have ).

[0121] The average particle diameter is defined as the particle size corresponding to 50% of the cumulative volume in the particle diameter size curve derived from the conductive powder using laser diffraction.

[0122] The conductive powder may include two types of conductive powder having different average particle diameters.

[0123] The average particle diameter is defined as the particle size corresponding to 50% of the volume accumulation in the particle size distribution curve of the conductive powder derived using laser diffraction.

[0124] The first conductive powder is 0.2 m 2 / g to 1.0 m 2 / g, 0.2 m 2 / g to 0.9 m 2 / g, 0.3 m 2 / g to 0.9 m 2 / g or 0.3 m 2 / g to 0.7 m 2 It can have a specific surface area of ​​ / g.

[0125] The second conductive powder is 0.8 m 2 / g to 2.0 m 2 / g, 0.8 m 2 / g to 1.8 m 2 / g, 0.8 m 2 / g to 1.6 m 2 / g, or 0.8 m 2 / g to 1.5 m 2 It can have a specific surface area of ​​ / g.

[0126] The specific surface area can be determined by taking approximately 2 g of conductive powder as a sample, degassing it at 60 ± 5°C for 10 minutes, measuring the total surface area using an automatic specific surface area measuring device (BET method), weighing the sample amount, and calculating it according to the formula below:

[0127]

[0128] If the conductive powder contains two types of conductive powder having an average particle diameter within the above range, the thermal conductivity and heat dissipation characteristics can be further improved.

[0129] The conductive powder can be surface-treated with a surface treatment agent. The surface treatment agent may include C10 to C20 fatty acids. Examples of fatty acids include capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, arachidic acid, myristoleic acid, palmitolic acid, sapienoic acid, oleic acid, elaidic acid, basenoic acid, linoleic acid, linolerid acid, arachidonic acid, eicosapentaenoic acid, α-linolenic acid, etc.

[0130] The conductive powder may have a loss on ignition (Ig-loss) of about 0.8 wt% or less, about 0.7 wt% or less, about 0.6 wt% or less, about 0.5 wt% or less, about 0.4 wt% or less, about 0.3 wt% or less, about 0.2 wt% or more, or about 0.01 wt% or more to about 0.4 wt%. The loss on ignition can be performed and measured at about 538°C for about 1 hour.

[0131] The surface of the conductive powder can be effectively treated with only a small amount of surface treatment agent. In other words, the conductive powder has a relatively low tap density and a large specific surface area, and can be surface-treated with only a small amount of surface treatment agent. Therefore, the conductive powder can be uniformly dispersed in the organic polysiloxane and improve the thermal bonding of the conductive filler. That is, because the dispersibility of the conductive powder is improved, the conductive powder can be added to the organic polysiloxane in a high concentration.

[0132] The silicone-based resin composition may include a conductive filler in an amount of about 300 to about 1,000 parts by weight, about 400 to about 900 parts by weight, or about 500 to about 800 parts by weight, based on 100 parts by weight of organic polysiloxane. When these ranges are satisfied, appropriate adhesion to the substrate can be maintained, and durability can be improved by preventing voids and cracks caused by thermal shock.

[0133] Figure 1 is a cross-sectional view illustrating the process of measuring the wrap shear strength and bond separation length of a silicone-based resin composition.

[0134] Referring to FIG. 1, a silicone-based resin composition (30) with a thickness of about 200 μm is coated onto a specific area of ​​the first nickel plate (20), and then the silicone-based resin composition (30) coated is covered with the second nickel plate (10). Next, the silicone-based resin composition (30) is cured at about 150°C for about 2 hours. The area coated with the silicone-based resin composition (30) may be about 2.5 cm x 1.25 cm. Then, the first nickel plate (20) and the second nickel plate (10) are pulled horizontally in opposite directions using a universal testing machine. Here, the horizontal stress is measured on the first nickel plate (20) and the second nickel plate (10) according to the length of the horizontal deformation.

[0135] The lap shear strength may be the value obtained by dividing the maximum stress value applied to the first nickel plate (20) and the second nickel plate (10) by the coating area of ​​the silicone resin composition (30).

[0136] The bond separation length may be the length deformed in the horizontal direction at the maximum stress value applied to the first nickel plate (20) and the second nickel plate (10).

[0137] The lap shear strength measured according to DIN EN 1465 is 0.5 N / mm 2 Above, 0.6 N / mm 2 Above, 0.7 N / mm 2 Above, 0.8 N / mm 2 Greater than, or 0.5 N / mm 2 Up to 1.5 N / mm 2 It could be.

[0138] The bond separation length measured according to DIN EN 1465 may be 0.3 mm or more, 0.4 mm or more, 0.5 mm or more, or 0.5 mm to 1.0 mm.

[0139] If these ranges are met, both the bonding stability and the heat dissipation characteristics of the thermal conductive layer can be improved.

[0140] The shear modulus expressed by the following equation is 1 N / mm 3 It may be greater than or equal to 3 N / mm or less:

[0141]

[0142] In the equation, LSS represents the lap shear strength of the silicone resin composition when measured according to DIN EN 1465, and JSL represents the bond separation length of the silicone resin composition when measured according to DIN EN 1465.

[0143] The shear modulus is 1 N / mm 3 ≥3 N / mm 3 Less than 1.1 N / mm 3 ≥3 N / mm 3Less than 1.3 N / mm 3 ≥2.5 N / mm 3 Less than or equal to 1.6 N / mm 3 ≥2.5 N / mm 3 It may be less than.

[0144] If these ranges are satisfied, deformation and delamination due to shear stress can be suppressed, and deformation caused by external thermal shock can be easily restored.

[0145] When measured according to measurement method 2 below, the coverage rate of the silicone-based resin composition may be 90% or more, 92% or more, 94% or more, 96% or more, or 99% or more.

[0146] [Measurement Method 2]

[0147] 1) A silicone-based resin composition is coated onto a first silicon substrate with dimensions of 27 mm x 27 mm at a weight of 0.7 g.

[0148] 2) A second silicon substrate of the same or larger size as the first silicon substrate is placed on the coated silicon-based resin composition, and then the silicon-based resin composition is cured while compressed by a force of 3 kgf.

[0149] 3) The area where the first silicon substrate is in close contact with the second silicon substrate is derived by the cured silicon-based resin composition.

[0150] 4) The coverage ratio is the ratio of the area of ​​the first silicon substrate in contact with the second silicon substrate to the planar area of ​​the first silicon substrate.

[0151] In addition, the thickness of the cured resin composition layer may be the spread thickness.

[0152] Since the silicone-based resin composition has the above coverage rate and spreading thickness, when the silicone-based resin composition is used as a thermal conductive layer in a semiconductor device, the thermal conductive layer can make close contact with the semiconductor package and heat dissipation part over a wide area and can have high thermal conductivity characteristics.

[0153] The viscosity of the silicone-based resin composition may be 50,000 cPs to 200,000 cPs, 50,000 cPs to 180,000 cPs, 70,000 cPs to 180,000 cPs, or 70,000 cPs to 150,000 cPs.

[0154] The viscosity of the silicone-based resin composition can be measured according to the DIN EN ISO 3219 method at about 25°C using a rheometer MCR302 (manufacturer: Anton Paar GmbH) equipped with a plate with a diameter of about 25 mm. Here, a shear rate of about 10 (1 / s) can be applied to measure the viscosity.

[0155] If these ranges are satisfied, an appropriate coverage rate and spreading thickness can be obtained.

[0156] The pot life of the silicone-based resin composition may be 10 to 16 hours, 10 to 15 hours, 10 to 14 hours, or 10 to 13 hours.

[0157] Available time can be measured by the following methods.

[0158] The silicone-based resin composition is left at room temperature. Then, the usable time is determined by measuring the time it takes for the viscosity of the silicone-based resin composition to increase by 50% compared to the initial viscosity.

[0159] The relative ratio of the change in thermal conductivity to the change in Shore A hardness of the silicone-based resin composition measured by the following measurement method may be 40% or less.

[0160] [measurement method]

[0161] 1) Silicone-based resin composition at 165°C and 26 kgf / cm² 2 A sheet is manufactured by hot-press forming for 15 minutes under pressure conditions.

[0162] 2) The sheet is cured at 150°C for 5 minutes to produce a first cured product. The Shore A hardness of the first cured product is measured according to ASTM D-2240, and the thermal conductivity is measured at 25°C according to ISO 22007-2.

[0163] 3) The first cured product is cured at 150°C for 120 minutes to produce the second cured product. The Shore A hardness of the second cured product is measured according to ASTM D-2240, and the thermal conductivity is measured at 25°C according to ISO 22007-2.

[0164] 4) Calculate the relative ratio of the change in thermal conductivity to the change in Shore A hardness according to Equation 1 below:

[0165]

[0166] In the equation, H1 represents the Shore A hardness of the first hardened product, H2 represents the Shore A hardness of the second hardened product, and TC H1 represents the thermal conductivity (W / mK) at H1, and TC H2 represents the thermal conductivity (W / mK) in H2.

[0167] In a silicone-based resin composition, the relative ratio of the change in thermal conductivity to the change in Shore A hardness measured by a measurement method may be 35% or less, 30% or less, 25% or less, 20% or less, 10% or less, 5% or less, or 1% or less.

[0168] Differences in hardness may occur in products manufactured from silicone-based resin compositions depending on the curing temperature, curing time, or composition of the silicone-based resin composition.

[0169] Since the relative ratio of the change in thermal conductivity to the change in Shore A hardness measured by the measurement method of the silicone-based resin composition is 40% or less, the change in thermal conductivity to the change in hardness is significantly reduced, and a thermal conductivity value capable of performing an appropriate heat dissipation function is obtained. Even if a change in hardness occurs in a product manufactured with the silicone-based resin composition, the change in thermal conductivity is small, so reliability can be improved when applying a product that needs to perform a heat dissipation function.

[0170] The Shore A hardness according to ASTM D-2240 of a cured product of a silicone-based resin composition may be 95 or less, 85 or less, 75 or less, 65 or less, 60 or less, 10 to 60 or less, 20 to 60 or less, or 30 to 60 or less. When the hardness is within this range, the occurrence of wear or cracking during product manufacturing can be minimized.

[0171] A silicone-based resin composition can satisfy the following formula:

[0172]

[0173] In the equation, X represents the Shore A hardness according to ASTM D-2240 of the cured product of the silicone resin composition, Y represents the thermal conductivity at 25°C according to ISO 22007-2 of the cured product of the silicone resin composition, and Y is 6 W / mK to 8 W / mK.

[0174] The coefficient of determination of X (R) in the range of 3 to 57 2 ) can be 0.95 or higher.

[0175] The equation represents a linear trend line where Shore A hardness is the variable X and thermal conductivity, the dependent variable based on X, is Y. The linear trend line can be derived using Microsoft Excel, and the coefficient of determination (R²) 2) can be obtained from the linear trend line. The coefficient of determination is a statistical term, a measure of the goodness of fit of a well-known regression equation, and represents the data Y of the dependent variable Y. i Y regarding i It represents the ratio of the sum of variations to the total sum of variations. The coefficient of determination is generally R 2 It is indicated as such, and the goodness of fit of the regression equation increases as the coefficient of determination approaches 1.

[0176] For example, in the equation, Y is 6.6 to 7.4 in the range where X is 3 to 57, which means that the thermal conductivity is 6.6 W / mK to 7.4 W / mK in the range where Shore A hardness is 3 to 57. Here, the coefficient of determination (R 2 ) indicates a value of 0.95 or higher. Therefore, even if there is a large change in hardness, the change in thermal conductivity is relatively small, which indicates a high goodness of fit of the regression equation. Accordingly, a silicone-based resin composition satisfying the equation can satisfy the reliability of product performance because there is little change in thermal conductivity even with a change in hardness.

[0177] The silicone-based resin composition includes a curing catalyst.

[0178] Curing catalysts can accelerate the curing of silicone-based resin compositions.

[0179] Examples of curing catalysts include organic titanate esters such as platinum-divinyltetramethyldisiloxane complex, tetrabutyl titanate, and tetraisopropyl titanate; organic titanium chelate compounds such as diisopropoxybis(acetylacetate)titanium and diisopropoxybis(ethylacetoacetate)titanium; organic aluminum compounds such as aluminum tris(acetylacetonate) and aluminum tris(ethylacetoacetate); organic zirconium compounds such as zirconium tetra(acetylacetonate) and zirconium tetrabutylate; organic tin compounds such as dibutyltin dioctoeate, dibutyltin dilaurate, and butyltin-2-ethylhexoate; and metal salts of organic carboxylic acids such as tin naphthenate, tin oleate, tin butyrate, cobalt naphthenate, and zinc stearate. Amine compounds such as hexylamine and dodecylamine phosphate and their salts; quaternary ammonium salts such as benzyltriethylammonium acetate; lower fatty acid salts of alkali metals such as potassium acetate; dialkylhydroxylamines such as dimethylhydroxylamine and diethylhydroxylamine; and guanidyl group-containing organosilicon compounds.

[0180] The silicone-based resin composition may include a curing catalyst in an amount of about 0.01 to about 5 parts by weight, about 0.03 to about 3 parts by weight, or about 0.1 to about 2 parts by weight, based on 100 parts by weight of organic polysiloxane.

[0181] The silicone-based resin composition may further include an adhesive.

[0182] The adhesive may include an alkoxysilane. Additionally, the adhesive may include an epoxy group. The adhesive may be at least one selected from the group consisting of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, and 3-glycidoxypropyltriethoxysilane.

[0183] The silicone-based resin composition may include an adhesive in an amount of about 1 to about 20 parts by weight, about 1 to about 10 parts by weight, or about 2 to about 8 parts by weight, based on 100 parts by weight of organic polysiloxane. The adhesive can improve the adhesion between the organic polysiloxane and the conductive filler.

[0184] The silicone-based resin composition may further include a reaction inhibitor. The reaction inhibitor may be at least one selected from the group consisting of acetylene compounds such as 2-methyl-3-butyn-2-ol, 2-phenyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol; en-phosphorus compounds such as 3-methyl-3-pentene-1-phosphorus and 3,5-dimethyl-3-hexene-1-phosphorus; curing reaction inhibitors such as hydrazine-based compounds, phosphine-based compounds, and mercaptan-based compounds.

[0185] The silicone-based resin composition may include a reaction inhibitor in an amount of about 0.0001 to about 10 parts by weight based on 100 parts by weight of organic polysiloxane.

[0186] The method for manufacturing a silicone-based resin composition may use known manufacturing methods and is not particularly limited.

[0187] For example, a silicone-based resin composition can be prepared by mixing an organic polysiloxane, a conductive filler, a curing catalyst, an adhesive, a reaction inhibitor, etc., for 30 minutes to 4 hours using a mixer such as Trimix, Tweenmix, Planetary Mixer (all manufactured by Inoue Seisakusho Co., Ltd., registered trademark); Ultramixer (manufactured by Mizuho Kogyo Co., Ltd., registered trademark); or Hibiscus Disperser Mix (manufactured by Primix Co., Ltd., registered trademark). In the mixing process, the process temperature may be about 0°C to about 25°C.

[0188] FIG. 2 is a cross-sectional view illustrating a cross-section of a semiconductor device according to an embodiment of the present invention.

[0189] Referring to FIG. 2, a semiconductor device according to the present invention includes a semiconductor package (200), a heat dissipation portion (400) disposed on the semiconductor package (200), and a heat conductive layer (500) interposed between the semiconductor package (200) and the heat dissipation portion (400).

[0190] The semiconductor device may include a circuit board (100) and a conductive bump (300).

[0191] The circuit board (100) can support a semiconductor package (200), a conductive bump (300), a heat dissipation part (400), and a thermal conductive layer (500).

[0192] The circuit board (100) may include circuit patterns. The circuit board (100) may include a plurality of circuit patterns disposed inside a flat body having a predetermined strength and comprising an insulating and heat-resistant material. Additionally, the circuit board (100) may include connection pads disposed on the body and electrically connected to the circuit patterns.

[0193] The main body of the circuit board (100) may include a thermosetting resin-based substrate, such as an epoxy resin substrate or a polyimide substrate, a flat plate, or a flat plate to which a heat-resistant organic film, such as a liquid crystal polyester film or a polyamide film, is attached. A circuit pattern may be arranged in a pattern form inside the main body and may include power wiring for power supply, ground wiring, and signal wiring for signal transmission. Each wiring may be arranged separated from one another by a plurality of interlayer insulating films formed on the upper and lower surfaces of the main body.

[0194] The connection pad can be exposed to the outside from the upper surface of the main body and connected to the circuit pattern. Accordingly, the external connection main body connected to the circuit board (100) can be electrically connected to the internal circuit pattern through the connection pad.

[0195] Various electronic components may be mounted on the connection pads included in the circuit board (100). The circuit board (100) may be a system board on which electronic components, including a semiconductor package (200), are mounted.

[0196] The semiconductor package (200) can be mounted on the circuit board (100). The semiconductor package (200) can be placed on the circuit board (100). The semiconductor package (200) can be connected to the circuit board (100) through a conductive bump (300).

[0197] A semiconductor package (200) may include a semiconductor chip including an integrated circuit, a semiconductor package substrate connected to the semiconductor chip, a conductive solder connecting the semiconductor chip and the semiconductor package substrate, and a sealing portion that seals the semiconductor chip and the conductive solder. The sealing portion may include a resin composition such as epoxy molding.

[0198] The semiconductor package (200) may be a memory device, a central processing unit, etc.

[0199] A conductive bump (300) can be placed between a semiconductor package (200) and a circuit board (100). The conductive bump (300) can electrically connect the semiconductor package (200) and the circuit board (100) to each other. The conductive bump (300) can be electrically connected to the semiconductor package (200) and a connection pad.

[0200] The heat dissipation portion (400) may be placed on the semiconductor package (200). The heat dissipation portion (400) may cover the semiconductor package (200). The heat dissipation portion (400) may be bonded to the circuit board (100). The heat dissipation portion (400) may cover the side of the semiconductor package (200).

[0201] The heat dissipation part (400) may include a conductor. The heat dissipation part (400) may include a metal. The heat dissipation part (400) may be thermally connected to an external heat dissipation fin.

[0202] The heat dissipation unit (400) can protect the semiconductor package (200) from external physical shock. The heat dissipation unit (400) can protect the semiconductor package (200) from external electromagnetic waves. That is, the heat dissipation unit (400) can block external electromagnetic waves.

[0203] The thermal conductive layer (500) can be placed between the semiconductor package (200) and the heat dissipation portion (400). The thermal conductive layer (500) can be in direct contact with the semiconductor package (200) and the heat dissipation portion (400). The thermal conductive layer (500) can be in close contact with the semiconductor package (200) and the heat dissipation portion (400).

[0204] The thermal conductive layer (500) can be thermally connected to the semiconductor package (200) and the heat dissipation part (400). That is, the thermal conductive layer (500) can transfer heat generated in the semiconductor package (200) to the heat dissipation part (400).

[0205] The thickness of the thermal conductive layer (500) may be about 1 μm to about 100 μm, about 2 μm to about 70 μm, about 5 μm to about 60 μm, or about 10 μm to about 40 μm.

[0206] The thermal conductive layer (500) comprises a silicone-based resin composition, the silicone-based resin composition comprises an organic polysiloxane, a conductive filler, and a curing catalyst, the conductive filler comprises a dendrite-type conductive powder having a main axis with an average length of 20 μm to 50 μm and a plurality of subaxiss branched from the main axis, and the thermal conductivity value per unit volume expressed by Equation 1 below is 10 to 40:

[0207]

[0208] In Equation 1, V is the volume ratio of the conductive filler to the total volume of the silicone-based resin composition and is a unitless value, and TC is the thermal conductivity measured by the measurement method 1 below and is a unitless value:

[0209] [Measurement Method 1]

[0210] 1) A silicone-based resin composition is molded into a size of 30 mm x 30 mm x 4 mm by a heat press.

[0211] 2) Next, the sample is prepared by curing it at 150°C for 2 hours.

[0212] 3) Measure the thermal conductivity of the sample at 25℃ according to ISO 22007-2.

[0213] The silicone-based resin composition may be the same as the silicone-based resin composition described above. The conductive filler of the silicone-based composition comprises a dendrite-type conductive powder comprising a main axis having an average length of 20 μm to 50 μm and a plurality of sub-axiss branched from the main axis, and when the thermal conductivity value per unit volume expressed by Equation 1 satisfies 10 to 40, the thermal conductive layer (500) containing the silicone-based composition can achieve high thermal conductivity even if it contains a small amount of conductive filler. In addition, the thermal conductive layer (500) can maintain appropriate adhesion to the semiconductor package (200) and the heat dissipation part (400), thereby improving the heat dissipation function.

[0214] The method of manufacturing a semiconductor device may use known manufacturing methods and is not particularly limited.

[0215] First, a semiconductor package (200) can be mounted on a circuit board (100) by means of a conductive bump (300). Next, a silicon-based resin composition can be coated on the semiconductor package (200). Alternatively, a silicon-based resin composition can be coated on the lower surface of a heat dissipation portion (400).

[0216] Next, the heat dissipation portion (400) can cover the semiconductor package (200). Accordingly, the coated silicone-based resin composition can come into direct contact with the lower surface of the heat dissipation portion (400) and the upper surface of the semiconductor package (200), and the curable silicone resin composition can be cured at a temperature of about 80°C or higher under a pressure of about 0.01 MPa or higher.

[0217] The pressure during the curing process may be about 0.01 MPa or higher. The pressure during the curing process may be about 0.05 MPa to about 100 MPa. The pressure during the curing process may be about 0.1 MPa to about 100 MPa.

[0218] The temperature in the curing process may be about 110°C to about 300°C. The temperature in the curing process may be about 120°C to about 300°C. The temperature in the curing process may be about 140°C to about 300°C. The curing time in the curing process may be about 30 minutes to about 20 hours. The thermal conductive layer (500) may be formed by this process.

[0219] The present invention will be explained in more detail below through examples and comparative examples. However, the following examples and comparative examples are merely illustrative for further explaining the present invention, and the present invention is not limited by the following examples and comparative examples.

[0220] Examples

[0221] - Organopolysiloxane #1: A compound represented by the following Formula 4, having a viscosity of 20,000 cPs at 23°C and containing silicon-bonded alkenyl groups:

[0222]

[0223] - Organopolysiloxane #2: A compound represented by the following Formula 6, having a viscosity of 1,000 cPs at 23°C and comprising a structure in which hydrogen groups are bonded to both ends:

[0224]

[0225] - Organopolysiloxane #3: A compound represented by the following formula 8, having a viscosity of 1,000 cPs at 23°C and comprising a structure in which hydrogen groups are bonded to the side chains:

[0226]

[0227] - Conductive Filler #1: Average particle diameter (D 50 ) is approximately 15 μm, the aspect ratio is approximately 12, the average principal axis length is approximately 30 μm, and the specific surface area is approximately 0.5 m² 2 / g, tap density is approximately 1 g / cm³ 3 Indigo-type silver powder

[0228] - Conductive Filler #2: Average Particle Diameter (D 50 ) is approximately 10 μm, aspect ratio is approximately 20, average principal axis length is approximately 22 μm, and specific surface area is approximately 1.2 m² 2 / g, tap density is approximately 1.5 g / cm³ 3 Indigo-type silver powder

[0229] - Conductive Filler #3: Average Particle Diameter (D 50 The diameter is approximately 20 μm, the aspect ratio is approximately 15, the average principal axis length is approximately 45 μm, and the specific surface area is approximately 1 m² 2 / g, tap density is approximately 1.2 g / cm³ 3 Indigo-type silver powder

[0230] - Conductive Filler #4: Average Particle Diameter (D 50 The diameter is approximately 12 μm, the aspect ratio is approximately 20, the average principal axis length is approximately 35 μm, and the specific surface area is approximately 0.8 m² 2 / g, tap density is approximately 1.2 g / cm³ 3 Indigo-type silver powder

[0231] - Conductive Filler #5: Average Particle Diameter (D 50 ) is approximately 15 μm, the aspect ratio is approximately 12, the average principal axis length is approximately 30 μm, and the specific surface area is approximately 0.5 m² 2 / g, tap density is approximately 1 g / cm³ 3 Ego fatty acid surface-treated dendrite-type silver powder

[0232] - Conductive Filler #6: Average Particle Diameter (D 50 ) is approximately 10 μm, aspect ratio is approximately 20, average principal axis length is approximately 22 μm, and specific surface area is approximately 1.2 m²2 / g, tap density is approximately 1.5 g / cm³ 3 Ego fatty acid surface-treated dendrite-type silver powder

[0233] - Conductive Filler #7: Average Particle Diameter (D 50 ) is approximately 15 μm, the aspect ratio is approximately 10, the average principal axis length is approximately 12 μm, and the specific surface area is approximately 0.2 m² 2 / g, tap density is approximately 0.5 g / cm³ 3 Indigo-type silver powder

[0234] - Conductive Filler #8: Average Particle Diameter (D 50 ) is approximately 12 μm, aspect ratio is approximately 50, average principal axis length is approximately 60 μm, and specific surface area is approximately 3.5 m² 2 / g, tap density is approximately 2.5 g / cm³ 3 Indigo-type silver powder

[0235] - Conductive Filler #9: Average Particle Diameter (D 50 ) is approximately 2.5 μm, the aspect ratio is approximately 1.1, and the specific surface area is approximately 0.3 m² 2 / g, tap density is approximately 6.4 g / cm³ 3 Spherical silver powder

[0236] - Conductive Filler #10: Average particle diameter (D 50 ) is approximately 1.2 μm, the aspect ratio is approximately 11, and the specific surface area is approximately 0.4 m² 2 / g, tap density is approximately 5 g / cm³ 3 In flake-type silver powder

[0237] - Adhesive: 3-Glycidoxypropyltrimethoxysilane

[0238] - Curing catalyst: Platinum-divinyltetramethyldisiloxane complex

[0239] - Reaction inhibitor: 1-ethynyl-1-cyclohexanol

[0240] Examples 1 to 8 and Comparative Examples 1 to 4

[0241] Each of the compositions shown in Table 1 below was added to a planetary mixer and uniformly mixed at room temperature at a speed of about 40 rpm for 1 hour to prepare a silicone-based resin composition.

[0242]

[0243]

[0244] Experimental Example

[0245] Experimental Example 1 - Measurement of Thermal Conductivity per Unit Volume

[0246] The silicone-based resin compositions of Examples 1 to 8 and Comparative Examples 1 to 4 were molded to a size of 30 mm x 30 mm x 4 mm using a heat press. Next, samples were prepared by curing them at approximately 150°C for 2 hours. Subsequently, the thermal conductivity of the samples of Examples 1 to 8 and Comparative Examples 1 to 4 was measured at 25°C using a thermal conductivity analyzer (model name: TPS-2500S, manufacturer: Hot Disk AB) in accordance with ISO 22007-2. Separately, the volume ratio of the conductive filler to the silicone-based resin compositions of Examples 1 to 8 and Comparative Examples 1 to 4 was measured, and the thermal conductivity values ​​per unit volume based on the measured thermal conductivity and volume ratio are shown in Table 2 below.

[0247] Experimental Example 2 - Thermal Shock Test

[0248] The silicone-based resin compositions of Examples 1 to 8 and Comparative Examples 1 to 4 were left at -40°C for 30 minutes and at 125°C for 30 minutes. After repeating this cycle about 500 times, the thermal conductivity was measured in the same manner as in Experimental Example 1. The results are shown in Table 2 below.

[0249] Experimental Example 3 - Measurement of Wrap Shear Strength and Joint Separation Length

[0250] Each silicone-based resin composition of Examples 1 to 8 and Comparative Examples 1 to 4 was coated to a thickness of approximately 200 μm over an area of ​​approximately 2.5 cm x 1.25 cm on a first nickel plate, and then covered with a second nickel plate. Subsequently, the first and second nickel plates were pre-cured at 135°C for approximately 10 minutes while compressing them with a load of 3 kgf. Next, the lap shear strength and bond separation length were measured according to DIN EN 1465 by pulling the first and second nickel plates in opposite directions using a universal testing machine (tensile strength analyzer manufactured by ZwickRoell GmbH). The results are shown in Table 2 below.

[0251] Experimental Example 4 - Measurement of Coverage Rate and Spread Thickness

[0252] 0.7 g of each silicone-based resin composition of Examples 1 to 8 and Comparative Examples 1 to 4 was coated onto a first silicon substrate of approximately 27 mm x 27 mm, and then covered with a second silicon substrate of the same size as the first silicon substrate. Subsequently, the second silicon substrate was pre-cured at 135°C for approximately 10 minutes while applying a force of approximately 3 kgf. Then, it was cured at 150°C for approximately 2 hours. Next, the area in contact between the first silicon substrate and the second silicon substrate with the cured coating layer was measured using a SAT ultrasonic inspection device and an image particle analyzer, and the ratio of the contact area to the total planar area was calculated. The results are shown in Table 2 below.

[0253] Experimental Example 5 - Viscosity Measurement

[0254] The viscosity of each silicone-based resin composition of Examples 1 to 8 and Comparative Examples 1 to 4 was measured at approximately 25°C according to the DIN EN ISO 3219 method using a rheometer (product name: MCR302, manufacturer: Anton Paar GmbH) with a circular plate with a diameter of 25 mm. At this time, the viscosity was measured at a shear rate of approximately 10 (1 / s). The results are shown in Table 2 below.

[0255] Experimental Example 6 - Measurement of Available Time

[0256] After leaving each silicone-based resin composition of Examples 1 to 8 and Comparative Examples 1 to 4 at room temperature, the time required for the viscosity to increase by 50% relative to the initial viscosity was measured. The results are shown in Table 2 below.

[0257]

[0258] Referring to Tables 1 and 2, the silicone-based resin compositions of Examples 1 to 8 comprise a dendrite-type conductive powder comprising a main axis with an average length of 20 μm to 50 μm and a plurality of sub-axiss branched from this main axis, and satisfy a thermal conductivity value per unit volume of 10 to 40. Accordingly, it was confirmed that Examples 1 to 8 exhibit improved thermal conductivity and coverage even when used in relatively small amounts compared to Comparative Examples 1 to 4.

[0259] Therefore, the silicone-based resin compositions of Examples 1 to 8 can be coated with a uniform thickness between the semiconductor package and the heat dissipation portion, and have improved heat dissipation performance compared to the silicone-based resin compositions of Comparative Examples 1 to 4. Explanation of the symbols

[0260] 10: Second nickel plate 20: First nickel plate 30: Silicone-based resin composition 100: Circuit board 200: Semiconductor package 300: Conductive bump 400: Heat dissipation part 500: Thermal conductive layer

Claims

Claim 1 A silicone-based resin composition comprises an organic polysiloxane; a conductive filler; and a curing catalyst, wherein the conductive filler comprises a dendrite-type conductive powder comprising a main axis having an average length of 20 μm to 50 μm and a plurality of sub-axiss branched from the main axis, and the thermal conductivity value per unit volume of the silicone-based resin composition is expressed by Equation 1 below and is 10 to 40: In the equation, V is the volume ratio of the conductive filler to the total volume of the silicone-based resin composition and is a value excluding units, and TC is the thermal conductivity measured by the following measurement method 1 and is a value excluding units: [Measurement Method 1] 1) molding the silicone-based resin composition to a size of 30 mm x 30 mm x 4 mm by a heat press, 2) then, curing the molded silicone-based resin composition at 150°C for 2 hours to prepare a sample, and 3) measuring the thermal conductivity of the sample at 25°C according to ISO 22007-2, a silicone-based resin composition. Claim 2 In claim 1, the conductive powder is a silicone-based resin composition having an aspect ratio of 10 to 50. Claim 3 In claim 1, the conductive powder has a tap density of 2.0 g / cm³ 3 Silicone resin composition less than Claim 4 In paragraph 1, the conductive powder has an average particle diameter (D 50 A first conductive powder having a diameter of 10 μm to 20 μm and an average particle diameter (D 50 A silicone-based resin composition comprising a second conductive powder having a size of 1 μm or more and less than 10 μm. Claim 5 In paragraph 4, the first conductive powder has a specific surface area of ​​0.2 m² 2 / g to 1.0 m 2 Silicone resin composition with a content of / g. Claim 6 In paragraph 4, the second conductive powder has a specific surface area of ​​0.8 m² 2 / g to 2.0 m 2 Silicone resin composition with a content of / g. Claim 7 A silicone-based resin composition according to claim 1, wherein the thermal conductivity (TC) is 7 W / mK or higher. Claim 8 In claim 1, the lap shear strength of the silicone-based resin composition when measured according to DIN EN 1465 is 0.5 N / mm 2 A silicone-based resin composition. Claim 9 A silicone resin composition according to claim 8, wherein the bond separation length is 0.3 mm or more when measured according to DIN EN 1465. Claim 10 In claim 1, the coverage rate of the silicone-based resin composition is 90% or more when measured by the following measurement method 2: [Measurement Method 2] 1) coating a silicone-based resin composition with a weight of 0.7 g onto a first silicon substrate of size 27 mm x 27 mm, 2) placing a second silicon substrate of the same or larger size as the first silicon substrate onto the coated silicone-based resin composition, and then curing the silicone-based resin composition while compressed by a force of 3 kgf, 3) deriving the area where the first silicon substrate is in contact with the second silicon substrate by the cured silicone-based resin composition, and 4) the coverage rate is the ratio of the area of ​​the first silicon substrate in contact with the second silicon substrate to the planar area of ​​the first silicon substrate. Claim 11 A semiconductor device comprises: a semiconductor package; a heat dissipation portion disposed on the semiconductor package; and a thermal conductive layer interposed between the semiconductor package and the heat dissipation portion, wherein the thermal conductive layer comprises a silicon-based resin composition, the silicon-based resin composition comprises an organic polysiloxane, a conductive filler, and a curing catalyst, and the conductive filler comprises a dendrite-type conductive powder comprising a main axis having an average length of 20 μm to 50 μm and a plurality of sub-axiss branched from the main axis, wherein the thermal conductivity value per unit volume of the silicon-based resin composition is expressed by Equation 1 below and is 10 to 40: In the equation, V is the volume ratio of the conductive filler to the total volume of the silicone-based resin composition and is a value excluding units, and TC is the thermal conductivity measured by the following measurement method 1 and is a value excluding units: [Measurement Method 1] 1) molding a silicone-based resin composition to a size of 30 mm x 30 mm x 4 mm by a heat press, 2) then, curing the molded silicone-based resin composition at 150°C for 2 hours to prepare a sample, and 3) measuring the thermal conductivity of the sample at 25°C according to ISO 22007-2, a semiconductor device.